2013
DOI: 10.1111/mcn.12017
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study exploring parental accounts of feeding pre‐school children in two low‐income populations in the UK

Abstract: Good nutrition in the early years of life is essential, yet the diets of many pre-school children in the UK are known to be poor. Understanding the decisions parents make when feeding young children is very important in determining what type and nature of interventional support may be developed to promote good nutrition. The aim of this study was to explore using qualitative methods, parental perceptions of feeding their children in order to inform the development of a nutrition intervention. Focus groups (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 37 publications
1
64
0
Order By: Relevance
“…Five samples (1, 2, 5, 6, 7) concerned UK populations and three (3, 4, 8) concerned US populations. It has recently been suggested that children's diets are poor in the UK, particularly among socially disadvantaged groups and these children tend to have lower intakes of fruit and vegetables and higher intakes of non-milk sugars (Hayter et al, 2013). It has also been suggested in the UK that "how parents feed their children has been underrepresented in obesity policy" (Clark, Goyder, Bissell, Blank, & Peters, 2007) and this may account for the concentration of studies regarding parental feeding in the UK over the last 5 years.…”
Section: Synthesis Of Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five samples (1, 2, 5, 6, 7) concerned UK populations and three (3, 4, 8) concerned US populations. It has recently been suggested that children's diets are poor in the UK, particularly among socially disadvantaged groups and these children tend to have lower intakes of fruit and vegetables and higher intakes of non-milk sugars (Hayter et al, 2013). It has also been suggested in the UK that "how parents feed their children has been underrepresented in obesity policy" (Clark, Goyder, Bissell, Blank, & Peters, 2007) and this may account for the concentration of studies regarding parental feeding in the UK over the last 5 years.…”
Section: Synthesis Of Findingsmentioning
confidence: 99%
“…To illustrate each theme, selected participant quotations are included. Those studies which contained good detail of participant quotes (such as Carnell et al, 2011;Hayter et al, 2013;and Herman et al, 2012) …”
Section: Synthesis Of Findingsmentioning
confidence: 99%
See 3 more Smart Citations